Prenatal Nicotine Exposure Induces Low Birthweight and Hyperinsulinemia in Male Rats - Nemoto, Takahiro; Ando, Hisae; Nagao, Mototsugu; Kakinuma, Yoshihiko; Sugihara, Hitoshi (Frontiers in Endocrinology, 2021)
Smoking during pregnancy is one of the causes of low birthweight. Ingestion of nicotine during pregnancy has various metabolic impacts on the fetus and offspring. According to the developmental origins of health and disease theory, low birthweight is a risk factor for developing various non-communicable diseases, including diabetes. We hypothesized that when nicotine-induced low-birthweight rats, when exposed to a high-fat diet (HFD) after growth, are predisposed to glucose intolerance as a result of a mismatch between the eutrophic environment and small body size. Therefore, we investigated whether hyperinsulinemia was caused by exposure of nicotine-induced low-birthweight rats to HFD, including whether this phenomenon exhibited possible sex differences. The average birthweight and body weight at weaning day of offspring from nicotine-administered dams was lower than those of controls. The offspring from nicotine-administered dams did not show rapid fat accumulation after exposure to HFD, and weight and body fat ratio of these animals did not differ from those of the controls. Blood glucose levels did not differ between the groups, but insulin levels increased only in male HFD-exposed offspring from nicotine-administered dams. Similarly, only in HFD-exposed male from nicotine-administered dams showed decreases in the insulin receptor expression in the liver. We conclude that male rats subjected to prenatal nicotine exposure develop hyperinsulinemia when exposed to HFD after growth. Our results suggest that decreased expression of insulin receptors in the liver may be involved in the mechanism underlying hyperinsulinemia in low-birthweight offspring, a phenomenon that appeared to exhibit a sex-specific bias.